Enhanced attention capture by emotional stimuli in mild traumatic brain injury - Exposito, Veronica (2015)
Mild traumatic brain injury (mTBI) may be associated with compromised executive functioning and altered emotional reactivity. Despite frequent affective and cognitive symptoms in mTBI, objective evidence for brain dysfunction is often lacking. Previously we have reported compromised performance in symptomatic mTBI patients in an executive reaction time (RT) test, a computer-based RT test engaging several executive functions simultaneously. Here, we investigated the cognitive control processes in mTBI in context of threat-related stimuli. We used behavioral measures and event-related potentials (ERP) to investigate attentional capture by task-relevant and task-irrelevant emotional stimuli during a Go-NoGo task requiring cognitive control. We also assessed subjective cognitive, somatic, and emotional symptoms with questionnaires. Twenty-seven subjects with previous mTBI and 17 controls with previous ankle injury participated in the study over 9 months post-injury. Electroencephalogram (EEG) was recorded while patients performed a modified executive RT-test. N2-P3 ERP component was used as a general measure of allocated attentional and executive processing resources. Although at the time of the testing, the mTBI and the control groups did not differ in symptom endorsement, mTBI patients reported having had more emotional symptoms overall since the injury than controls. The overall RT-test performance levels did not differ between groups. However, when threat-related emotional stimuli were used as Go-signals, the mTBI group was faster than the control group. In comparison to neutral stimuli, threat-related stimuli were associated with increased N2-P3 amplitude in all conditions. This threat-related enhancement of the N2-P3 complex was greater in mTBI patients than in controls in response to Go signals and NoGo signals, independent of relevance. We conclude that mTBI may be associated with enhanced attentional and executive resource allocation to threat-related stimuli. Along with behavioral evidence for enhanced attention allocation to threat stimuli, increased brain responses to threat were observed in mTBI. Enhanced attention capture by threat-related emotional stimuli may reflect inefficient top-down control of bottom-up influences of emotion, and might contribute to affective symptoms in mTBI.